2020
DOI: 10.7150/thno.50663
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into ferroptosis: Implications for age-related diseases

Abstract: Rapid increase in aging populations is an urgent problem because older adults are more likely to suffer from disabilities and age-related diseases (ARDs), burdening healthcare systems and society in general. ARDs are characterized by the progressive deterioration of tissues and organs over time, eventually leading to tissue and organ failure. To date, there are no effective interventions to prevent the progression of ARDs. Hence, there is an urgent need for new treatment strategies. Ferroptosis, an iron-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 239 publications
(156 reference statements)
1
51
0
Order By: Relevance
“…It also proceeds in the absence of the key components of necroptosis, such as MLKL, RIPK1 and RIPK3. Early studies have suggested that regulated forms of cell death contribute significantly to the pathogenesis of CVDs, including cardiomyopathy, MI and HF 65 , 66 . Although it remains unclear whether ferroptosis is an independent form of cell death or whether it acts to amplify necrotic cell death, the molecules that mediate ferroptosis may provide new therapeutic targets for CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…It also proceeds in the absence of the key components of necroptosis, such as MLKL, RIPK1 and RIPK3. Early studies have suggested that regulated forms of cell death contribute significantly to the pathogenesis of CVDs, including cardiomyopathy, MI and HF 65 , 66 . Although it remains unclear whether ferroptosis is an independent form of cell death or whether it acts to amplify necrotic cell death, the molecules that mediate ferroptosis may provide new therapeutic targets for CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is implicated in a variety of human diseases, such as myocardial infarction, atherosclerosis, kidney diseases, liver diseases, and neuronal diseases, as well summarized in recent review articles [ 22 , 97 , 98 , 99 , 100 ]. Numerous ferroptosis inhibitors, including ferrostatin-1, liproxstatin-1, vitamin E analogs, and iron chelators, have been shown to effectively ameliorate disease symptoms in mouse models of each disease [ 22 , 97 , 98 , 99 ]. In this review, we discussed the underlying mechanism of lipid peroxidation in ferroptosis and the various lipid metabolic pathways that control lipid peroxidation and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis can be induced by several ferroptosis-inducing compounds (FINs) [ 22 , 23 ]. Erastin is the first identified FIN that inhibits the cystine/glutamate antiporter (system x c − ), thereby resulting in the depletion of glutathione (GSH), a cofactor for GPX4 ( Figure 1 ) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these measures have limited success, and there are no effective intervention or treatment measures to protect the brain against cell death [169,170]. Accumulating evidence demonstrates that ferroptosis accelerates ischemic stroke, and ferroptosis inhibition can significantly reduce disease severity and facilitate functional recovery [170]. Deferoxamine (DFO), an iron chelator widely used to treat iron overload, reduces the cerebral infarct volume in MCAO rats and suppresses ferroptosis by promoting erythropoietin synthesis and increasing hypoxia-inducible factor-alpha (HIF-α) levels [24].…”
Section: Pharmacotherapies For Ischemic Stroke Targeting Ferroptosis and Necroptosismentioning
confidence: 99%